2014 IEEE International Conference on Image Processing (ICIP) 2014
DOI: 10.1109/icip.2014.7025985
|View full text |Cite
|
Sign up to set email alerts
|

Image processing for materials characterization: Issues, challenges and opportunities

Abstract: This introductory paper aims at summarizing some problems and state-of-the-art techniques encountered in image processing for material analysis and design. Developing generic methods for this purpose is a complex task given the variability of the different image acquisition modalities (optical, scanning or transmission electron microscopy; surface analysis instrumentation, electron tomography, micro-tomography. . . ), and material composition (porous, fibrous, granular, hard materials, membranes, surfaces and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Instead of finding each maximin edge ( 2 ) times, we can calculate how many times each MST edge appears in the sum, which can be calculated with a modification of Kruskal's minimum spanning tree algorithm. In recent work we presented pseudo-code based on the disjoint set data-structures [25].…”
Section: Supervised Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of finding each maximin edge ( 2 ) times, we can calculate how many times each MST edge appears in the sum, which can be calculated with a modification of Kruskal's minimum spanning tree algorithm. In recent work we presented pseudo-code based on the disjoint set data-structures [25].…”
Section: Supervised Segmentationmentioning
confidence: 99%
“…Accurate segmentation of materials images introduces additional challenges to those encountered in other domains (e.g. bio-medical) and has been the topic of a recent special session [2] and recent references [3,4]. Some of these challenges include:…”
Section: Introductionmentioning
confidence: 98%
“…It uses modal convolution to describe the CNN and uses it to extract inter‐modal and modal information and fuse features at the pixel level. Couprie et al 20 proposed a multi‐scale CNN for RGB‐D scene markers based on hierarchical feature method. Liao et al designed a static gesture recognition system combining depth image and color image, 21 using depth image and color image acquired by Realsense, combined with generalized Hough transform to map depth image to color image.…”
Section: Related Workmentioning
confidence: 99%
“…The overlap of grayscale values between particle and matrix is displayed in the histogram in Figure 5c. The parameterization for all three segmentation methods for the René 104 image are as follows: the Otsu thresholding value was determined to be 0.498, the energy exchange parameter for EM/MPM ( β in reference Duval et al (2014)) was found to be 1.7, with 5 iteration/segmentation loops performed, and the graph-cutting procedure had values of λ = 6.0, β = 0, α γ = 1.0, ω γ = 1 e −2 , α γ = 1.0 and , respectively. The ground truth image was obtained through meticulous use of MS Paint.…”
Section: Image Segmentationmentioning
confidence: 99%
“…The analysis and post-processing of materials characterization datasets are often more challenging and time-consuming than the acquisition of the raw data (Duval et al, 2014). For example, image segmentation, or the problem of automatically separating and classifying features of interest from the background, is a common analysis task where it is trivial to complete by the human eye but often difficult for a computer to reliably and repeatably accomplish.…”
Section: Introductionmentioning
confidence: 99%